2000
DOI: 10.1159/000010205
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Sonographic Visualization of Fetal Skeleton in the Second Trimester of Pregnancy

Abstract: Purpose: To demonstrate the potential of using three-dimensional (3D) sonography to reveal anomalies of fetal skeleton. Materials and Methods: Forty-two normal fetuses and 3 anencephalic fetuses from 14 to 27 weeks’ gestation were studied with a specially developed abdominal 3D transducer (3.5 MHz). This imaging system provided conventional two-dimensional (2D) sonographic images and also generated within seconds high-quality 3D images in the surface and transparent mode with no need for an external workstatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Although portions of many sutures and fontanelles were identified at 18 to 23 weeks of gestation, it was difficult to assess the structural continuity of sutures and fontanelles with 2DUS in a single plane owing to cranial curvature (Patel et al, 1994). Real-time 2DUS scanning, sweeping through the fetal skull and 3DUS, showing the curvilinear structure of the cranium in a single image may ease visualization of larger portions of sutures and fontanelles (Pretorius and Nelson, 1994;Yanagihara and Hata, 2000). The data on comparing these modalities in evaluating the normal appearance of the sutures and fontaneles prenatally are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although portions of many sutures and fontanelles were identified at 18 to 23 weeks of gestation, it was difficult to assess the structural continuity of sutures and fontanelles with 2DUS in a single plane owing to cranial curvature (Patel et al, 1994). Real-time 2DUS scanning, sweeping through the fetal skull and 3DUS, showing the curvilinear structure of the cranium in a single image may ease visualization of larger portions of sutures and fontanelles (Pretorius and Nelson, 1994;Yanagihara and Hata, 2000). The data on comparing these modalities in evaluating the normal appearance of the sutures and fontaneles prenatally are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…However, upon reexamination of the 2DUS, they were identified, but only after viewing the 3DUS images (Pretorius and Nelson, 1994). Yanagihara and Hata (2000) studied 42 normal fetuses and 3 anencephalic fetuses ranging from 14 to 27 weeks of gestation. They obtained 2DUS and 3DUS images of the fetal skeleton including the skull.…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors regard detection rates for accurate assessment of skeletal dysplasias as almost equal between 2DUS and 3DUS, they do claim that the improved visualization of the dysplasia by 3DUS makes it a useful addition to standard 2DUS. 168,169 Most authors report improvement of diagnostic accuracy: Garjian et al 170 173 reported improvement in diagnostic accuracy in recognizing skeletal dysplasia in 35 fetuses with 2DUS and 3DUS (respectively 51.4% and 77.1%). The authors mention especially the assistance of 3DUS in spatial orientation; the fetus and its skeleton can be viewed from different angles and can be rotated in all directions to obtain the best image.…”
Section: Skeleton Skull and Spinementioning
confidence: 99%
“…This provides a survey view of the foetal skeleton, with a demonstration of normal or abnormal ossification ( Fig. 3a-c) [21,22]. In the minimum mode, only the minimum gray levels of the ROI are displayed.…”
Section: Gray Render Modesmentioning
confidence: 99%
“…11) [14]. The transparent mode provides a view of the foetal skeleton, with demonstrations of abnormal ossification and abnormalities of the spine [14,22] and long limb bones [11,14,15]. 3D and 4D foetal echocardiography using STIC and, in particular, STIC-Colour allows the examiner to view complex anomalies of the foetal heart and to control the cardiac blood flow during different heart cycles ( Fig.…”
Section: Detection Of Foetal Malformationsmentioning
confidence: 99%